Social Innovation Approach in Integrated Farming: Advancing Rural Well-Being in Karawang Regency, West Java, Indonesia - Arifa, Sheila Hauna; Fahmi, Fikri Zul (Universitas Muhammadiyah Yogyakarta, 2025)
Integrated farming systems represent innovative solutions designed to improve farmers’ well-being by increasing income and improving livelihoods in rural communities. By integrating social innovation strategies, this approach helps to promote economic welfare and address challenges such as poverty and limited access to resources. This study delves into the impact of integrated farming, a form of social innovation, on the well-being of rural communities in the Global South. The study centers on Mas Ihsan Bersaudara Farm in Karawang, Indonesia, serving as a compelling case study. An in-depth exploration was conducted within the farm community by including all employees as participants, thereby facilitating comprehensive insights. While integrated farming exhibited characteristics associated with social innovation and enhanced productivity, this study’s findings revealed that its influence on well-being lacked statistical significance. Structural equation modeling (SEM) shed light on the intricate relationships between variables. The findings uncovered that production behavior and management exerted a more substantial impact on productivity than factors directly tied to social innovation. Specifically, productivity accounted for 13.5% of overall well-being, emphasizing that heightened productivity alone did not unilaterally elevate farmers’ well-being. This study has underscored the need for a holistic approach, one transcending mere productivity gains. Key elements included market accessibility, equitable pricing mechanisms, educational interventions, and robust social support systems. By addressing the multifaceted aspects of community life through a combination of direct field surveys that captured farmers’ firsthand perspectives and advanced statistical analysis using SEM, this study contributes to sustainable rural development.